INTERVENSI LAYANAN BIMBINGAN KONSELING TERHADAP PERMASALAHAN- PERMASALAHAN SISWA DI SEKOLAH GUIDANCE COUNSELING INTERVENTIONS ON STUDENT PROBLEM AT SCHOOL - Bella Disa Novita; Zulkipli Lessy (Bajang Institute, 2024)
Education is very important and must be obtained by all Indonesian people, which aims to educate the nation's life and improve the quality of Indonesian people's resources. Education is divided into two kinds, namely, formal and informal education. Formal education is obtained by students from schools, while informal education is obtained from families and the environment. In pursuing formal education at school, students certainly experience various problems, and this will have an impact on student academics. Through guidance and counseling services in schools can help students to solve various problems. But the fact is that there are still many schools that do not provide guidance and counseling services in schools. Even though this has been regulated in the Regulation of the Minister of Education and Culture of the Republic of Indonesia number 111 of 2014 concerning the importance of guidance and counseling services. This article discusses the intervention of guidance and counseling services in schools to help students who experience various problems in order to support their academic achievement. Reviewed with literature review research methods from various journal articles regarding the intervention of guidance and counseling services in schools. As well as formulating steps that can be taken to procure counseling guidance services in Indonesian schools.